Evaluation of English Language Policy In The Education System In Indonesia - Alya Audria; Zaitun Qamariah (BADAN PENERBIT STIEPARI PRESS, 2023)
This article examines the implementation of the English Language Policy in Indonesian schools and its positive and negative outcomes. The policy was established in the 1960s to assist students in learning English for academic and employment purposes. While the policy has led to increased access to learning resources and improved curriculum guidelines, challenges such as limited funding, inadequate teacher training, and a lack of standardized assessment methods hinder its full effectiveness. Additionally, resource disparities between urban and rural areas contribute to unequal access to quality English language education. To address these challenges, recommendations are proposed. These include increasing funding for English language education, enhancing teacher training programs, developing standardized assessment methods, promoting authentic language practice, addressing resource disparities, and collaborating with international institutions. These measures aim to improve the implementation of the policy, enhance students' English language proficiency, and create a more equitable education system. Regular evaluation, stakeholder involvement, and policy adjustments are crucial for the continuous improvement of the English Language Policy in Indonesia.